Internalization of Moderation in The Characteristics of Islamic Law: Application Case Study Moderation of the Muslim in Kab. Ketapang - Bahrul Ulum; Abubakar Yokobu; Miskari Ahmad (Institut Kariman Wirayudha Sumenep, 2023)
Study This will study life public lively Ketapang Muslims in pluralism religious and multi- ethnic However still hold on stick to the teachings their respective religions and remains guard tolerance in religion, especially for the Islamic ummah is the majority religion, however keep internalizing _ values moderation in messages teachings of Islamic sharia. This study will give understanding and concepts original sourced _ from the Koran and Hadith, then translated by the scholars so be structured characteristics Islamic law is moderate and becomes Rahmah on natural universe. Research purposes This is so that every Modern Muslims can understand and implement values moderation in life every day, you can interact with Good with non - Muslims around, no need to hesitate with application laws the Islam he believes in. So that what he did No considered contradictory with Islamic law with correct and comprehensive in his life daily. Study This use method literature and observations in the field to behavior and application values moderation in accordance with characteristics sourced Islamic law from the Al-Qur'an, As-Sunnah and classical and modern books from classical and contemporary scholars who are qualified and expert in the field. Research result This found that life public Ketapang Muslims highly respect it tall moderation religious especially ummah Islam, which is internalized values moderation based on characteristics Islamic law